A heuristic approach for a multi-period capacitated single-allocation hub location problem - Wemans, Ana Margarida Cordeiro de Sousa (2017)
Tese de mestrado, Estatística e Investigação Operacional (Investigação Operacional) Universidade de Lisboa, Faculdade de Ciências, 2016